SEARCH AND ELIMINATION OF REPEATED CONNECTIONS IN THE SCHEME OF GUIDING SLIDE-CRANK MECHANISM OF THE GRIPPING DEVICE - Pogrebnyak, R. P.; Pohrebniak, M. R. (Science and Transport Progress, 2020)
Purpose. The article is aimed to carry out a structural analysis of the coupled straight-guiding crank-slide mechanism of variable structure gripping devices with external unilateral constraints. It is also necessary to determine the number of internal and external repeating connections in the contours of the mechanism at different stages of its functioning, to assess their possible perniciousness and to suggest ways to reduce them. Methodology. Achieving this goal is carried out based on the universal structural theory of Ozols mechanisms for analyzing the gripping device as a mechanism with geometric, internal and frictional holonomic external constraints. Ozols internal and external structural formulas are used. Findings. The eleven-link gripping device is built on the basis of coupled central parallelogram crank-slider mechanism with a driving cranks. Synchronous driving cranks act on elongated connecting rods connected to sliders and gripping clamp elements. Gripping clamp elements carry out plane-parallel movement. Structural analysis was performed using structural schemes for two states of the mechanism: before clamping the object and in the state of the clamped object. In the first state of the mechanism with kinematic pairs of class V, the one-movable scheme contains thirteen internal redundant constraints. In the second state of the mechanism, external constraints act and in the scheme another five additional external repeating constraints are formed. Their contour arrangement and possible consequences of their action are shown. Originality. Structural analysis of the coupled crank-slider mechanism of the gripping device as a mechanism of a variable structure with internal and external connections is carried out for the first time. It is performed contour analysis, search and elimination, as well as reduction of pernicious repeated connections in the internal and external contour of the mechanism. Practical value. Practical recommendations have been developed on changing the mobilities of sliding pairs to eliminate all repeated connections in the internal contours of the mechanism. To reduce the number of pernicious repeated connections, the introduction of a self-centering unloading coupling into the external contour of the mechanism is proposed.